REPRESENTASI ASPEK PERLAWANAN PADA DOMINASI PATRIARKI BUDAYA BALI DALAM KARYA I GAK MURNIASIH DAN CITRA SASMITA - Fika Khoirun Nisa (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2021)
In the current Indonesian art discourse, the reading of works is no longer limited only to the results of the analysis and interpretation of formal elements, but also considering the relationship with the socio-cultural factors of artists so as to give a picture of the multifaceted character of art. This study was designed to identify the representation of resistance aspects in the dominance of Balinese cultural patriarchy in Indonesian fine art and interpret its symbols. The artists whose works were chosen as a case study in this study are I Gusti Ayu Kadek Murniasih and Citra Sasmita. This study used a multidisciplinary approach (Feminism and Semiotics). Based on the results of the analysis, the aspect of resistance is represented through visual symbols that are typical in the two works of artists tend to be born from the experience of the environment that is close to everyday life to a traumatic experience that gives birth to pain and fear. For both of them, painting is a catharsis process and as a medium to transform ideas and alignments so that the message to be conveyed can reach a wider scope.